PENGARUH PRICE DISCOUNT, BONUS PACK, DAN INSTORE DISPLAY TERHADAP IMPULSE BUYING PADA TOKO A.FAUZI PEKANBARU - Dino Aulia; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to find out how big the influence of price discount, bonus pack and instore display against impulse buying. The samples on this research taken as many as 100 respondents and techniques used is probability sampling. The data in this study using the method of accidental sampling through a questionnaire filled out by visitors. Data retrieved using simple regression analysis and multiple regression analysis. The results of this research show the price discount effect significantly to impulse buying. Bonus pack effect significantly to impulse buying. Instore display effect significantly to impulse buying. And simultaneous price discount, bonus pack and instore display has an impact on impulse buying.Keywords: price discount, bonus pack, instore displays, impulse buying